Exploring the Impact of Foreign Labor on Local Employee Performance in Garment Companies to Support Economic Growth - Purnomo, Joko; Sujoko, Sujoko; Hartadi , Agung (International Journal of Economics Development Research (IJEDR), 2024)
This study aims to explore the effect of foreign labor on the performance of local employees in garments companies through a literature review approach. In recent years, many garments companies have integrated foreign labor to improve efficiency and global competitiveness. However, the impact of foreign labor on local employee performance remains a controversial topic. By analyzing various relevant literatures, this study identifies the factors that influence the relationship between foreign labor and local employee performance, both directly and indirectly. The review shows that foreign labor can improve technical skills and introduce new technologies that have the potential to increase productivity. However, this can also lead to competition in the workplace which leads to a decrease in the morale and motivation of local employees. In addition, cultural influences and social dynamics in the work environment are important aspects in the relationship between foreign labor and local employees. This research provides a deeper understanding of the interaction between the two workforce groups and its implications for local employee performance. The findings are expected to provide recommendations for human resource managers in designing more effective policies in managing workforce diversity in garments companies.